2012
DOI: 10.1080/10627197.2012.735921
|View full text |Cite
|
Sign up to set email alerts
|

Not Read, but Nevertheless Solved? Three Experiments on PIRLS Multiple Choice Reading Comprehension Test Items

Abstract: Multiple-choice (MC) reading comprehension test items comprise three components: text passage, questions about the text, and MC answers. The construct validity of this format has been repeatedly criticized. In three between-subjects experiments, fourth graders (N 1 D 230, N 2 D 340, N 3 D 194) worked on three versions of MC items from the Progress in International Reading Literacy Study 2001 reading comprehension test with relevant components successively deleted: "original version" (text, questions, MC-answer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
0
6
0
2
Order By: Relevance
“…Neither the inherent limitations of MC items (e.g., MC is not suited for the assessment and discussion of opinions; cf. Haladyna & Rodriguez, 2013) nor possible distractor-related biases (Sparfeldt et al, 2012) seem to affect the corresponding aspects of a valid competence assessment.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Neither the inherent limitations of MC items (e.g., MC is not suited for the assessment and discussion of opinions; cf. Haladyna & Rodriguez, 2013) nor possible distractor-related biases (Sparfeldt et al, 2012) seem to affect the corresponding aspects of a valid competence assessment.…”
Section: Discussionmentioning
confidence: 98%
“…For example, in TIMSS 2007 (4th grade), most items stand alone (151 out of 179). This could be relevant, because the questions and the set of choices in reading items seem to provide contextual information that sometimes facilitates finding the correct option (e.g., Sparfeldt, Kimmel, Löwenkamp, Steingräber, & Rost, 2012).…”
Section: Studymentioning
confidence: 99%
“…B. Lindner et al, 2015;Sparfeldt, Kimmel, Löwenkamp, Steingräber & Rost, 2012). Wenn Prüfende nicht die zeitlichen Kapazitäten haben, um sicherzustellen, dass hochwertige und weitgehend fehlerfreie geschlossene Aufgaben erstellt werden können, sollte auf den Einsatz geschlossener Aufgaben verzichtet werden.…”
Section: Testbearbeitungsstrategienunclassified
“…Albeit generally rare, this approach was sometimes chosen in the domain of reading comprehension (e.g., Katz, Lautenschläger, Blackburn, & Harris, 1990; Rost & Sparfeldt, 2007; Schroeder & Tiffin-Richards, 2014; Sparfeldt, Kimmel, Löwenkamp, Steingräber, & Rost, 2012). These authors found that – across several multiple-choice reading comprehension tests – omitting the text still resulted in correct responses above chance level.…”
Section: Validity and Validationmentioning
confidence: 99%